Novel Guanidine Compound against Multidrug-Resistant Cystic Fibrosis-Associated Bacterial Species - Saeed, Aamer (2018)
Chronic pulmonary infection is a hallmark of lung disease in cystic fibrosis (CF). Infections dominated by non-fermentative Gram-negative bacilli are particularly difficult to treat and highlight an urgent need for the development of new class of agents to combat these infections. In this work, a small library comprising thiourea and guanidine derivatives with low molecular weight was designed; these derivatives were studied as antimicrobial agents against Gram-positive, Gram-negative, and a panel of drug-resistant clinical isolates recovered from patients with CF. One novel compound, a guanidine derivative bearing adamantane-1-carbonyl and 2-bromo-4,6-difluouro-phenyl substituents (H-BDF), showed potent bactericidal activity against the strains tested, at levels generally higher than those exhibited by tobramycin, ceftazimide and meropenem. The role that different substituents exert in the antimicrobial activity has been determined, highlighting the importance of the halo-phenyl group in the guanidine moiety. The new compound displays low levels of cytotoxicity against THP-1 and A549 cells with a selective index (SI) > 8 (patent application PCT/IB2017/054870, August 2017). Taken together, our results indicate that H-BDF can be considered as a promising antimicrobial agent.